Photodynamic and chemotherapy synergistic antibacterial composite material as well as preparation method and application thereof
By using photosensitizer i-ZnPPOPs to load a composite of calcium peroxide and gentamicin in photodynamic therapy, combined with high dietary fiber, the inefficiency and hypoxia of photodynamic therapy in the treatment of wound infections is solved, and the problem of photodynamic therapy is achieved. More efficient antibacterial effects and wound healing.
Patent Information
- Application Number
- CN202411257145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
When treating wound infection, existing photodynamic therapies are difficult to achieve efficient antibacterial effects due to the short ROS diffusion distance, local hypoxia and poor biosafety of photosensitizers, and ignore the regulation of inflammatory factors, resulting in hindering wound healing.
The composite material of photosensitizer i-ZnPPOPs loaded with calcium peroxide and gentamicin is used to coat hyaluronic acid and combine with high dietary fiber to improve the targeting and antibacterial effect of photodynamic therapy and promote wound healing.
It improves the antibacterial effect of photodynamic therapy, relieves hypoxia from infected wounds, promotes wound healing and tissue regeneration, and enhances the targeting of bacteria and the efficiency of chemotherapy.
Smart Images

Figure CN119113109A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a composite material for synergistic antibacterial activity of photodynamic therapy and chemotherapy, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] In the human body, skin tissue is the largest, most exposed, and most vulnerable tissue. Once skin tissue is damaged, the repair process is very complex, including four classic stages: hemostasis, inflammation, proliferation, and remodeling. And during the skin healing process, pathogens can easily invade and form colonies, leading to serious wound infections, which prolongs the inflammatory stage and hinders wound healing. Antibiotic-based therapy has always been a common means of treating infections, but this easily leads to bacterial resistance.
[0004] Many new methods for treating wound infection have been reported. Among them, photodynamic therapy (PDT) has become one of the most attractive treatment methods due to its advantages such as accurate spatiotemporal control, low toxicity and side effects, and no bacterial resistance. It has broad application prospects in preclinical / clinical research. As an effective non-invasive antibacterial treatment strategy, PDT combines two separate non-toxic components, photosensitizer (PS) and laser, to generate O through electron transfer. 2- , OH, O2 2- , generated by energy transfer 1 O2, a highly cytotoxic reactive oxygen species (ROS), can destroy the bacterial membrane structure, thereby achieving bacterial eradication. However, due to the short diffusion distance of ROS and severe hypoxia at the local infection site, it is difficult to achieve efficient photodynamic therapy. In addition, the poor biosafety and poor light absorption capacity of photosensitizers usually have a negative impact on PDT, which may hinder wound healing. Furthermore, the lack of selectivity of photosensitizers for bacteria also restricts the application of PDT in the body.
[0005] At the same time, however, current wound healing strategies mainly focus on the removal of microorganisms, while ignoring the regulation of inflammatory factors in the human body. The immune system is the most effective defense system against pathogen invasion. It can respond to inflammation caused by pathogenic microorganisms and maintain the stability and physiological balance of the body's internal environment. Recent studies have shown that intestinal flora is closely related to many inflammatory diseases, such as diabetes, sepsis, joint inflammation, inflammatory bowel disease, and respiratory allergies. The intestinal microbiota represents a "forgotten organ" that performs many physiological functions and is of great significance to human biology. The fermentation of dietary fiber by intestinal flora can produce short-chain fatty acids (SCFAs) such as acetate, propionate, and butyrate, which have significant anti-inflammatory effects on both colonic epithelium and immune cells. SCFAs can effectively bind to the "metabolite sensing" G protein-coupled receptor 43 (GPR43) highly expressed in neutrophils, regulating inflammatory responses by increasing the number of immune cells. Therefore, high dietary fiber intake helps to increase the metabolism of SCFAs, thereby providing more binding sites for GPR43 to recruit immune cells, becoming a key regulator of inflammatory diseases. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, and a preparation method and application thereof.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, the composite material comprising an intermediate composite material and hyaluronic acid (HA) coated on the outside of the intermediate composite material, wherein the intermediate composite material is based on the photosensitizer i-ZnPPOPs and loaded with calcium peroxide and gentamicin (Gen);
[0009] The structural formula of the photosensitizer i-ZnPPOPs is shown in formula (I):
[0010]
[0011] The second aspect of the present invention provides a method for preparing the composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, comprising:
[0012] (1) photosensitizer i-ZnPPOPs, calcium peroxide nanoparticles and gentamicin are dispersed in an organic solvent and stirred to obtain an intermediate composite material;
[0013] (2) dispersing the intermediate composite material in a hyaluronic acid solution and stirring to obtain a composite material having synergistic antibacterial effects of photodynamic therapy and chemotherapy.
[0014] The third aspect of the present invention provides use of the composite material of the first aspect and / or the composite material prepared by the preparation method of the second aspect in the preparation of antibacterial drugs.
[0015] The fourth aspect of the present invention provides an antibacterial drug, comprising the composite material described in the first aspect and / or the composite material prepared by the preparation method of the second aspect.
[0016] The fifth aspect of the present invention provides an antibacterial pharmaceutical composition, comprising the composite material described in the first aspect and / or the composite material prepared by the preparation method of the second aspect and high dietary fiber.
[0017] The beneficial effects of the present invention are:
[0018] (1) The present invention provides a composite material Gen-BioCa / i-ZnPPOPs@HA for synergistic antibacterial effect of photodynamic therapy and chemotherapy, wherein the composite material Gen-BioCa / i-ZnPPOPs@HA includes an intermediate composite material Gen-BioCa / i-ZnPPOPs and hyaluronic acid HA coated on the outside of the intermediate composite material Gen-BioCa / i-ZnPPOPs, wherein the intermediate composite material Gen-BioCa / i-ZnPPOPs is a substrate with photosensitizer i-ZnPPOPs, loaded with calcium peroxide and gentamicin Gen. The composite material Gen-BioCa / i-ZnPPOPs@HA has excellent characteristics of targeting bacteria and antibacterial effect. Specifically, hyaluronic acid can target hyaluronidase secreted by bacteria to capture bacteria, and then transfer the intermediate composite material Gen-BioCa / i-ZnPPOPs@HA to the bacterial surface and interact with the negatively charged bacterial membrane. Subsequently, the exposed biomass-based CaO2 (BioCa) was released and reacted with water to generate H2O2 and O2, thereby alleviating the hypoxia of the infected wound and effectively promoting the healing of the i-ZnPPOPs. 1 The production of O2 further enhances the antibacterial effect of photodynamic therapy. At the same time, the released gentamicin can further enhance the antibacterial efficiency of chemotherapy.
[0019] (2) The composite material Gen-BioCa / i-ZnPPOPs@HA combined with high dietary fiber can effectively accelerate angiogenesis and collagen deposition, providing a promising strategy for accelerating wound healing and tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0021] Figure 1Scanning electron microscopy for BioCa;
[0022] Figure 2 The preparation process of the composite material Gen-BioCa / i-ZnPPOPs@HA;
[0023] Figure 3 This is the scanning electron microscope image of the composite material Gen-BioCa / i-ZnPPOPs@HA;
[0024] Figure 4 IR spectrum (A) and solid-state NMR (B) of i-ZnPPOPs;
[0025] Figure 5 Thermogravimetric curve of the composite material Gen-BioCa / i-ZnPPOPs@HA;
[0026] Figure 6 The Zeta potential comparison diagram of i-ZnPPOPs and its building blocks;
[0027] Figure 7 A is the UV absorption and reflection spectra of porphyrin monomer and i-ZnPPOPs; B is the photocurrent of i-ZnPPOPs and Gen-BioCa / i-ZnPPOPs; C is the fluorescence spectra of i-ZnPPOPs, Gen-BioCa / i-ZnPPOPs and porphyrin monomer (I: i-ZnPPOPs, II: Gen-BioCa / i-ZnPPOPs, III: porphyrin monomer); D is the release of O2 under different treatments; E is the generation of H2O2; F is the fluorescence spectra of TEMP as the capture agent 1 ESR spectrum of O2;
[0028] Figure 8 A is Staphylococcus aureus treated with PBS; B is Staphylococcus aureus treated with Gen-BioCa / i-ZnPPOPs@HA; C is Escherichia coli treated with PBS; D is Escherichia coli treated with Gen-BioCa / i-ZnPPOPs@HA;
[0029] Fig. 9 The back wound healing of mice infected with Staphylococcus aureus under different treatment conditions; (I is PBS, II is Gen-BioCa / i-ZnPPOPs@HA, III is Gen-BioCa / i-ZnPPOPs@HA+high dietary fiber). DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0032] A first typical embodiment of the present invention provides a composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, the composite material comprising an intermediate composite material and hyaluronic acid coated on the outside of the intermediate composite material, wherein the intermediate composite material is based on the photosensitizer i-ZnPPOPs and loaded with calcium peroxide and gentamicin;
[0033] The structural formula of the photosensitizer i-ZnPPOPs is shown in formula (I):
[0034]
[0035] The composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy is spherical or quasi-spherical, and the average particle size of the base photosensitizer i-ZnPPOPs is about 1 micron. After loading calcium peroxide and gentamicin, the particle size of the composite material is larger than 1 micron.
[0036] A second typical embodiment of the present invention provides a method for preparing the composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, comprising:
[0037] (1) photosensitizer i-ZnPPOPs, calcium peroxide nanoparticles and gentamicin are dispersed in an organic solvent and stirred to obtain an intermediate composite material;
[0038] (2) dispersing the intermediate composite material in a hyaluronic acid solution and stirring to obtain a composite material having synergistic antibacterial effects of photodynamic therapy and chemotherapy.
[0039] In one or more embodiments, the preparation method of the photosensitizer i-ZnPPOPs comprises:
[0040] S1, dispersing compound 1 and pyrrole in a solvent, heating and stirring to react to obtain porphyrin-based ionic porous organic polymer i-PPOPs;
[0041] S2, dispersing the porphyrin-based ionic porous organic polymer i-PPOPs and zinc salt in an organic solvent, heating and stirring to obtain a photosensitizer i-ZnPPOPs;
[0042] The reaction routes include:
[0043]
[0044] Preferably, in step S1, the molar ratio of compound 1 to pyrrole is 1:2.5-3.5, preferably 1:3.
[0045] Preferably, in step S1, the solvent comprises propionic acid;
[0046] More preferably, in step S1, the concentration of compound 1 in propionic acid is 7.6-14.5 mmol / L, preferably 11.45 mmol / L.
[0047] Preferably, in step S1, the temperature of the heating and stirring reaction is 130-150° C., preferably 140° C.; the time of the heating and stirring reaction is 10-14 h, preferably 12 h.
[0048] Preferably, in step S2, the zinc salt comprises zinc chloride.
[0049] Preferably, in step S2, the mass ratio of the porphyrin-based ionic porous organic polymer i-PPOPs to the zinc salt is 0.8-1.2:0.8-2, preferably 1:1.
[0050] Preferably, in step S2, the organic solvent comprises DMF.
[0051] Further preferably, in step S2, the concentration of the porphyrin-based ionic porous organic polymer i-PPOPs in DMF is 4-6 g / L, preferably 5 g / L.
[0052] Preferably, in step S2, the temperature of the heating and stirring reaction is 130-150° C., preferably 140° C.; the time of the heating and stirring reaction is 5-8 h, preferably 6 h.
[0053] In one or more embodiments, in step (1), the method for preparing calcium peroxide nanoparticles comprises:
[0054] Add oyster shells to the inorganic acid, stir to react, and filter to collect the liquid;
[0055] Under the condition of continuous stirring, a mixture of ammonia water and polyethylene glycol is added to the collected liquid; then a hydrogen peroxide solution is added and stirring is continued. After the reaction is completed, the solid is collected, which is calcium peroxide nanoparticles.
[0056] In one or more embodiments, in step (1), the mass ratio of the photosensitizer i-ZnPPOPs, calcium peroxide nanoparticles and gentamicin is 9-12:4-6:1, preferably 10:5:1.
[0057] In one or more embodiments, in step (1), the organic solvent comprises methanol.
[0058] Preferably, the concentration of the photosensitizer i-ZnPPOPs in methanol is 9-11 g / L, preferably 10 g / L.
[0059] In one or more embodiments, in step (1), the stirring reaction time is 20 to 30 hours, preferably 24 hours.
[0060] In one or more embodiments, in step (2), the concentration of the hyaluronic acid solution is 4-6 mg / mL, preferably 5 mg / mL.
[0061] In one or more embodiments, in step (2), the stirring time is 3 to 5 hours, preferably 4 hours.
[0062] A third typical embodiment of the present invention provides use of the composite material of the first aspect and / or the composite material prepared by the preparation method of the second aspect in the preparation of antibacterial drugs.
[0063] A fourth typical embodiment of the present invention provides an antibacterial drug, comprising the composite material described in the first aspect and / or the composite material prepared by the preparation method of the second aspect.
[0064] In one or more embodiments, the antibacterial drug is in the form of a skin administration dosage form, such as an external solution, lotion, liniment, ointment, plaster, paste, patch, etc.
[0065] In one or more embodiments, the antibacterial drug further comprises at least one pharmaceutically acceptable excipient and / or carrier.
[0066] A fifth typical embodiment of the present invention provides an antibacterial pharmaceutical composition, comprising the composite material described in the first aspect and / or the composite material prepared by the preparation method of the second aspect and high dietary fiber.
[0067] In one or more embodiments, the high dietary fiber includes acetylated high amylose starch.
[0068] In one or more embodiments, the composite material of the first aspect and / or the composite material prepared by the preparation method of the second aspect is a skin administration dosage form, such as an external solution, lotion, liniment, ointment, plaster, paste, patch, etc.; the high dietary fiber is a gastrointestinal administration dosage form, preferably, the above-mentioned gastrointestinal administration dosage form includes powders, tablets, granules, capsules, sustained-release agents, solutions, dry suspensions, effervescent tablets, emulsions, suspensions, etc.
[0069] In one or more embodiments, the antibacterial pharmaceutical composition further comprises at least one pharmaceutically acceptable excipient and / or carrier.
[0070] The excipients of the present invention refer to ingredients other than the active ingredients in a pharmaceutical composition or pharmaceutical preparation, which are non-toxic to the subject. Commonly used excipients in the art include buffers, stabilizers, preservatives or excipients, and commonly used excipients include binders, fillers, wetting agents, disintegrants, etc.
[0071] As an example, the excipients that can be used in the preparation of the present invention include but are not limited to: the excipient is selected from calcium phosphate, magnesium stearate, talc, dextrin, starch, gel cellulose, methyl cellulose, carboxymethyl cellulose sodium salt and polyvinyl pyrrolidone.
[0072] The drug carrier of the present invention can be a pharmaceutically acceptable solvent, suspending agent, vesicle, nanomaterial, etc.
[0073] Those skilled in the art can prepare the compounds of the present invention into pharmaceutical compositions or preparations using known techniques. For example, any compound (at least one compound) disclosed in the above-mentioned first aspect of the present invention is mixed with a pharmaceutical excipient, and then, if necessary, the resulting mixture is formed into a desired shape. Except for those mentioned in the present invention, pharmaceutical preparations can also be prepared according to known pharmaceutical preparations. And, except for those mentioned in the present invention, suitable pharmaceutical excipients are known in the art, for example, referring to the 2005 edition of the Handbook of Pharmaceutical Excipients (Original Fourth Edition).
[0074] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0075] The CaO2 used in the following examples is extracted from oyster shells, and the specific extraction method includes:
[0076] Mix oyster shells (1.0 g) with 2.5 mL of hydrochloric acid (12 mol / L), stir at room temperature for 20 min, then add 2.5 mL of ultrapure water, and filter to remove the undissolved oyster shells. Then, under constant stirring, add a mixture of ammonia water (2.5 mL, 1 M) and polyethylene glycol 400 (PEG400) (30 mL) to the mixed solution within 10 minutes. Keeping the stirring condition unchanged, continue to add 2.5 mL of 30% H2O2 solution to the mixed solution, continue stirring for 20 min, and collect the solid by centrifugation (13000 rpm), which is CaO2 nanoparticles, hereinafter referred to as BioCa, and freeze-dry for later use. The scanning electron microscopy of BioCa is shown in the figure. Figure 1 As shown, the particle size of BioCa is about 25 nm.
[0077] The preparation method of acetylated high-amylose starch is the same as that of international patent application WO 02 / 02102A1.
[0078] Example 1
[0079] Figure 2 For the preparation process of the composite material Gen-BioCa / i-ZnPPOPs@HA, refer to Figure 2 Synthesized composite material Gen-BioCa / i-ZnPPOPs@HA.
[0080] 1.1 Porphyrin-based ionic porous organic polymer i-PPOPs was prepared by solvothermal method under N2 atmosphere. Compound 1 (400 mg, 0.458 mmol) and pyrrole (92 mg, 1.368 mmol) were dispersed in propionic acid (40 mL) and reacted at 140 °C for 12 h. The reaction was cooled to room temperature, filtered and collected, and washed with water and tetrahydrofuran, respectively, to obtain porphyrin-based ionic porous organic polymer i-PPOPs.
[0081] 1.2 Porphyrin-based ionic porous organic polymer i-PPOPs (100 mg) and zinc chloride (100.86 mg, 0.74 mmol) were dispersed in 20 mL DMF, stirred at 140 ° C for 6 h, cooled to room temperature, filtered and separated, and washed with DMF three times. After vacuum drying at 100 ° C, the photosensitizer i-ZnPPOPs was obtained with a yield of 82.1%. ICP-AES analysis showed that the Zn content was 3.58%.
[0082] The specific reaction routes include:
[0083]
[0084] 1.3 The photosensitizer i-ZnPPOPs (200 mg), CaO2 nanoparticles extracted from oyster shells (100 mg) and gentamicin (20 mg) were added to methanol (20 mL), ultrasonically dispersed for 20 min, stirred at room temperature overnight, and centrifuged at 9000 rpm to obtain the intermediate composite material Gen-BioCa / i-ZnPPOPs.
[0085] 1.4 The intermediate composite material Gen-BioCa / i-ZnPPOPs prepared in 1.3 was dispersed in a hyaluronic acid solution (5 mg / mL) and stirred continuously for 4 h. Finally, the solid was obtained by centrifugation and dried to obtain the composite material Gen-BioCa / i-ZnPPOPs@HA.
[0086] Figure 3 This is a scanning electron microscope image of the composite material Gen-BioCa / i-ZnPPOPs@HA. Figure 3 It can be seen that Gen and BioCa are distributed on the surface of i-ZnPPOPs, and i-ZnPPOPs has rich pore structure and high specific surface area.
[0087] Example 2
[0088] IR spectrum and solid-state NMR characterization of i-ZnPPOPs:
[0089] 2.1 i-ZnPPOPs were characterized by infrared spectroscopy, such as Figure 4 As shown in A, compared with the infrared spectrum of the raw material compound 1, the stretching vibration peak of C=O (1698cm -1 ) disappeared in the spectrum of i-ZnPPOP, indicating that compound 1 and pyrrole underwent an effective condensation reaction. The spectra of compound 1 and i-ZnPPOPs both have a peak at 1619 cm -1 A peak appears near 1002 cm-1, which is attributed to the stretching vibration of the imidazole unit C=N, indicating the presence of imidazole groups in the polymer. -1 There is a vibration peak at , which is the deformation of NH in the plane of the porphyrin macrocyclic ring, indicating the formation of the porphyrin ring.
[0090] 2.2 Pass 13 C NMR further confirmed the structural details of i-ZnPPOPs, such as Figure 4 As shown in B. Resonance peaks belonging to the porphyrin macrocycle appeared at 106.8ppm and 123.5ppm, indicating that the porphyrin unit was formed again. The other three chemical shifts were related to the aromatic carbon in the methylene (52.8ppm), benzene ring (129.5ppm) and imidazole ring (136.2ppm). In addition, at 1 3No signal of free aldehyde was observed in the C CP-MAS solid-state NMR spectrum. Combining the characterization results of FT-IR and NMR, the synthesis of i-ZnPPOPs can be inferred.
[0091] Example 3
[0092] Stability characterization of the composite material Gen-BioCa / i-ZnPPOPs@HA:
[0093] Figure 5 The thermogravimetric curve of the composite material Gen-BioCa / i-ZnPPOPs@HA shows that the composite material Gen-BioCa / i-ZnPPOPs@HA has good heat resistance. Under the protection of N2, when the temperature reaches 100°C, the weight loss rate is only 8%. Such high stability ensures that the composite material Gen-BioCa / i-ZnPPOPs@HA can withstand harsh environmental conditions.
[0094] Example 4
[0095] Characterization of surface charge of i-ZnPPOPs and its building blocks
[0096] Figure 6 This is a comparison diagram of the Zeta potential of i-ZnPPOPs and its building blocks. Figure 5 It can be seen that the Zeta potentials of i-PPOPs, BioCa and Gen are 24.3mV, 5.94mV and -24.03mV, respectively. Under the modification of CaO2 and Gen, the surface zeta potential of Gen-BioCa / i-ZnPPOPs becomes 14.60mV. After further modification with HA, the surface charge of Gen-BioCa / i-ZnPPOPs@HA becomes -19.5mV. The change of surface Zeta indicates the successful preparation of Gen-BioCa / i-ZnPPOPs@HA.
[0097] Example 5
[0098] Characterization of optical properties and oxygen release capacity of the composite material Gen-BioCa / i-ZnPPOPs@HA:
[0099] 5.1 Study on the light absorption capacity of porphyrin monomers and i-ZnPPOPs using UV-Vis-NIR diffuse reflectance spectroscopy and UV-Vis absorption spectroscopy. Figure 7 A. Compared with the narrow absorption band of porphyrin monomer (Formula II) at 420nm, the i-ZnPPOPs after polymerization have a significant red-shift tendency, with stronger absorption from ultraviolet to infrared. At the same time, a wide absorption edge generated by the extended π-conjugated network was also observed, even reaching 900nm. This will be beneficial for bacterial detection and wound treatment.
[0100]
[0101] 5.2 Photosensitizers usually undergo irreversible photobleaching under light irradiation, which will adversely affect their PDT performance. Therefore, the photophysical properties of i-ZnPPOPs and Gen-BioCa / i-ZnPPOPs were studied. First, the photocurrent responses of i-ZnPPOPs and Gen-BioCa / i-ZnPPOPs were detected by repeated on / off irradiation cycles. Both showed stable responses under light irradiation ( Figure 7 B). Next, the porphyrin monomer and i-ZnPPOPs were irradiated with light for 0, 10, and 30 minutes, and the changes in fluorescence intensity were monitored. Within 10 minutes, the fluorescence intensity of the porphyrin monomer decreased by 97.2%, while under the same experimental conditions, the fluorescence intensity of i-ZnPPOPs decreased by only 9.3% ( Figure 7 C). These results indicate that i-ZnPPOP and its composites have excellent photostability.
[0102] 5.3 Biomass calcium peroxide, as a highly biocompatible metal peroxide, can be decomposed into O2 and H2O2 in i-ZnPPOPs-mediated photodynamic therapy, alleviating hypoxia, increasing the efficiency of ROS generation, and amplifying the level of oxidative stress.
[0103] The release of O2 and H2O2 during the degradation of the materials was evaluated in PBS solution. When CaO2 NPs or Gen-BioCa / i-ZnPPOPs were dispersed in PBS, the O2 concentration increased rapidly, reaching nearly 18.4 mg / L ( Figure 7 D). As with Gen-BioCa / i-ZnPPOPs@HA, the cumulative amount of O2 remained almost unchanged even when the reaction time was extended to 3h. However, with the introduction of hyaluronic acid (HA), the release of O2 from the Gen-BioCa / i-ZnPPOPs@HA system increased dramatically. Apparently, the HA coating can effectively prevent the decomposition of CaO2 in water while intelligently controlling the release of the coated antimicrobial agent until the material reaches the infection site where HA is overexpressed. Similar results were also observed for the cumulative release of H2O2 in Gen-Gen-BioCa / i-ZnPPOPs@HA ( Figure 7 E). In order to verify the types of active oxygen in the catalytic process, ESR spectroscopy was used for analysis, and it was found that the reaction system contained a large amount of singlet oxygen, which showed a peak of 1:1:1. Figure 7 F.
[0104] Example 6
[0105] Characterization of antibacterial properties of Gen-BioCa / i-ZnPPOPs@HA
[0106] In order to test the antibacterial properties of Gen-BioCa / i-ZnPPOPs@HA, an in vitro antibacterial experiment was established. Two typical Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) were selected for research to explore the antibacterial ability of Gen-BioCa / i-ZnPPOPs@HA. Figure 8 As shown in A and 8B, the Staphylococcus aureus and Escherichia coli in the control group still maintained spherical and rod-shaped morphologies, with smooth surfaces and intact cell walls. However, after treatment with Gen-BioCa / i-ZnPPOPs@HA, obvious morphological changes and membrane damage were observed. The surface of Staphylococcus aureus was completely destroyed and the contents flowed out. Wrinkles and depressions appeared on the surface of Escherichia coli. These results indicate that Gen-BioCa / i-ZnPPOPs@HA can destroy the structure of the membrane. This may be attributed to the good photocatalytic properties of Gen-BioCa / i-ZnPPOPs@HA under light conditions, which can produce a large amount of reactive oxygen, accelerate bacterial cell membrane oxidation, and improve antibacterial efficiency.
[0107] Example 7
[0108] Characterization of wound healing performance of Gen-BioCa / i-ZnPPOPs@HA
[0109] Specific experimental process:
[0110] 6-8 week old mice (17-19 g) were intraperitoneally injected with streptozotocin (70 mg kg -1 ) was used to establish a diabetic mouse model. Blood was collected from the tail vein of the mouse and the blood glucose level was measured with a blood glucose meter. When the blood glucose level of the mouse was higher than 16.7mmol / L, the mouse diabetes model was established. Then a wound (5×5mm) was constructed on the epidermis of the back of the mouse, and 50μL of Staphylococcus aureus (1×10 6 CFU / mL) for 24 h to establish the diabetic wound infection model.
[0111] from Fig. 9 It can be seen that on the first day of the Staphylococcus aureus wound infection, different degrees of suppuration were found in each group, proving that the back wound was successfully infected with Staphylococcus aureus. PBS (Ⅰ), Gen-BioCa / i-ZnPPOPs@HA (Ⅱ) and Gen-BioCa / i-ZnPPOPs@HA+high dietary fiber (Ⅲ) were used to treat the infected wound. Specifically, PBS and Gen-BioCa / i-ZnPPOPs@HA were coated on the wound surface, and high dietary fiber was added to the mouse feed at an amount of 15wt%.
[0112] On day 9, the therapeutic effect of Gen-BioCa / i-ZnPPOPs@HA+high dietary fiber was significantly higher than that of the other groups, and on day 14, the wound was completely healed.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy, characterized in that: The composite material comprises an intermediate composite material and hyaluronic acid coated on the outside of the intermediate composite material, wherein the intermediate composite material uses the photosensitizer i-ZnPPOPs as a substrate and is loaded with calcium peroxide and gentamicin; The structural formula of the photosensitizer i-ZnPPOPs is shown in formula (I):
2. The method for preparing the composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy according to claim 1, characterized in that: include: (1) photosensitizer i-ZnPPOPs, calcium peroxide nanoparticles and gentamicin are dispersed in an organic solvent and stirred to obtain an intermediate composite material; (2) dispersing the intermediate composite material in a hyaluronic acid solution and stirring to obtain a composite material having synergistic antibacterial effects of photodynamic therapy and chemotherapy.
3. The preparation method according to claim 2, characterized in that: The preparation method of photosensitizer i-ZnPPOPs comprises: S1, dispersing compound 1 and pyrrole in a solvent, heating and stirring to react to obtain porphyrin-based ionic porous organic polymer i-PPOPs; S2, dispersing the porphyrin-based ionic porous organic polymer i-PPOPs and zinc salt in an organic solvent, heating and stirring to obtain a photosensitizer i-ZnPPOPs; The reaction routes include: 。 4. The preparation method according to claim 3, characterized in that: In step S1, the molar ratio of compound 1 to pyrrole is 1:2.5-3.5, preferably 1:3; Or, in step S1, the solvent includes propionic acid; Preferably, in step S1, the concentration of compound 1 in propionic acid is 7.6 to 14.5 mmol / L, preferably 11.45 mmol / L; Or, in step S1, the temperature of the heating and stirring reaction is 130-150° C., preferably 140° C.; the time of the heating and stirring reaction is 10-14 h, preferably 12 h; Or, in step S2, the zinc salt includes zinc chloride; Or, in step S2, the mass ratio of the porphyrin-based ionic porous organic polymer i-PPOPs to the zinc salt is 0.8-1.2:0.8-2, preferably 1:1; Or, in step S2, the organic solvent includes DMF; Preferably, in step S2, the concentration of the porphyrin-based ionic porous organic polymer i-PPOPs in DMF is 4 to 6 g / L, preferably 5 g / L; Alternatively, in step S2, the temperature of the heating and stirring reaction is 130-150° C., preferably 140° C.; the time of the heating and stirring reaction is 5-8 h, preferably 6 h.
5. The preparation method according to claim 2, characterized in that: In step (1), the method for preparing calcium peroxide nanoparticles comprises: Add oyster shells to the inorganic acid, stir to react, and filter to collect the liquid; Under the condition of continuous stirring, a mixture of ammonia water and polyethylene glycol is added to the collected liquid; then a hydrogen peroxide solution is added and stirring is continued. After the reaction is completed, a solid is collected, which is calcium peroxide nanoparticles; Or, in step (1), the mass ratio of the photosensitizer i-ZnPPOPs, calcium peroxide nanoparticles and gentamicin is: 9-12:4-6:1, preferably 10:5:1, Or, in step (1), the organic solvent comprises methanol; Preferably, the concentration of the photosensitizer i-ZnPPOPs in methanol is 9 to 11 g / L, preferably 10 g / L; Or, in step (1), the stirring reaction time is 20 to 30 hours, preferably 24 hours; Or, in step (2), the concentration of the hyaluronic acid solution is 4 to 6 mg / mL, preferably 5 mg / mL; Alternatively, in step (2), the stirring time is 3 to 5 hours, preferably 4 hours.
6. Use of the composite material for synergistic antibacterial effects of photodynamic therapy and chemotherapy as claimed in claim 1 and / or the composite material prepared by the preparation method as claimed in any one of claims 2 to 5 in the preparation of antibacterial drugs.
7. An antibacterial drug, characterized in that: The invention comprises the composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy as claimed in claim 1 and / or the composite material prepared by the preparation method as claimed in any one of claims 2 to 5.
8. The antibacterial drug according to claim 7, characterized in that The antibacterial drug is in the form of a skin administration dosage form.
9. An antibacterial drug composition, characterized in that: The invention comprises the composite material for synergistic antibacterial effect of photodynamic therapy and chemotherapy as claimed in claim 1 and / or the composite material prepared by the preparation method as claimed in any one of claims 2 to 5 and high dietary fiber.
10. The antibacterial drug composition according to claim 9, characterized in that: The high dietary fiber is acetylated high-amylose starch; Or, the composite material of photodynamic and chemotherapy synergistic antibacterial according to any one of claims 1 to 2 and / or the composite material prepared by the preparation method according to any one of claims 3 to 5 is a dosage form for skin administration; and the high dietary fiber is a dosage form for gastrointestinal administration.
Citation Information
Cited By
Composite material integrating sterilization and pain relieving as well as preparation method and application of composite material
CN119405657A
Composite drug-loaded nano particle based on calcium peroxide carrier and preparation method of composite drug-loaded nano particle
CN119656132A
